Investigation on in-situ deoxygenation performance of bio-oil model compound guaiacol over Ce-Fe/Al2O3 catalyst - Yang M; Chen Y; Wang Y; Yang L; Cui W; Liu Y; Wang C; Chen Q (Elsevier B V on behalf of Shandong University, 2023)
The investigation of the low-cost deoxygenation of guaiacol (GUA, a model bio-oil compound) is of importance for upgrading bio-oil. At present, common sulfide catalysts for GUA deoxygenation reactions cause contamination of the liquid product, and noble metal catalysts are economically disadvantageous. In this study, four reduced Fe-based oxides with different Ce doping ratios were prepared and their effects on the in-situ deoxygenation performance of GUA in aqueous/methanol hydrogen donor solvents were explored. The results based on the deoxygenation degree, conversion degree, and higher heating value (HHV) of the products showed that the oxide catalyst with a Fe/Ce molar ratio of 2:1 in the methanol solvent performed very well. After selecting an excellent catalyst and a better hydrogen donor solvent, four factors (reaction temperature, reaction time, volume ratio of GUA dosage and methanol dosage, and the ratio of catalyst dosage at the bottom of the reactor to that at the top) in the deoxygenation degree of GUA were investigated using an orthogonal experimental method to further explore the performance of the catalyst. The results showed that the reaction temperature and time greatly influenced GUA deoxygenation. Under optimal experimental conditions, the deoxygenation degree and conversion degree of GUA could reach 34.36% and 92.56%, respectively, based on the relative peak area of gas chromatography–mass spectrometry, and the HHV of the liquid product was 32.27 MJ/kg. Although Fe/Ce catalysts mainly promote demethoxylation, demethylation, and methylation, the stability and quality of the liquid products were improved compared with GUA owing to the reduction in phenolic hydroxyl and ether content. The reduced catalyst in the process of GUA in-situ deoxygenation reactions in methanol maintained a steady performance, as revealed by X-ray diffraction and X-ray fluorescence.
Keywords: Guaiacol; Fe-based catalyst modified by Ce; Deoxygenation; Reaction temperature; Reaction time